Pengaruh Pemberian Rendaman Kulit Bawang Merah (Allium cepa L.) dengan Media Tanam Ampas Tebu terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) - Siregar, Nuri Jannah Tussadiyah; Idris, M; Selvia, Irda Nila (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Pakcoy comes from the Brassicaceae family, known for being rich in nutrients, including vitamins A, C, K, as well as fibres and minerals. Onion skin contains bioactive compounds that have the potential to be organic fertilizers, while sugarcane bagasse is agricultural waste that can be used as an alternative planting medium. This study aims to determine the effect of soaking shallot skin using sugarcane bagasse planting media for the growth of Pakcoy (Brassica rapa L.). This study was conducted in Tuntungan II village using the factorial Randomized Block Design (RAK) method consisting of two factors and 3 replications with 3 treatment levels. The parameters observed included relative growth rate, net assimilation rate, number of leaves, total leaf area, wet weight and dry weight of pakcoy plants. The results showed that the combination of onion skin soaking gave a significant effect on all red parameters (B2: 250 ml/500 ml water) and bagasse gave a significant effect on the net assimilation rate of 2-3 MST and 4-5 MST in the treatment of 500 gr/polybag bagasse but on other parameters the control treatment was better. Thus, the provision of onion skin soaking as organic fertilizer with bagasse planting media on the growth of pakcoy plants can be applied in agriculture, because this treatment has a significant effect on all treatments.